Socialization of Compost Making from Rice Straw at Nagari Sijunjung Indigenous Village, West Sumatera - Fahrudin, Danil Eka; Arfah, Muh; Delamontano, Eldo; Bayu, Hikkal Ahmad; Firjatullah, Zahra; Hafidz, Muhammad; Fitri, Wanda Julianti; Istifaiyyah, Salma; Akbar, Afif; Muflihah, Asriani; Molieh, Candra Irawan Peto; Ridwan (Universitas Nahdlatul Ulama Surabaya, 2025)
Nagari Sijunjung Indigenous Village, located in Sijunjung Regency, is a community with substantial agricultural potential. Rice is one of the primary commodities cultivated in this village. Currently, rice farming relies on a rain-fed system, which is highly dependent on the rainy season, resulting in synchronized planting schedules. This practice significantly increases the volume of rice straw waste after the harvest season, while its utilization remains suboptimal. One viable solution to address this issue is processing rice straw into compost. The aim of this program was to enhance the knowledge and skills of local residents in composting rice straw. The socialization activity was attended by 14 participants from Nagari Sijunjung Indigenous Village. Pretests and posttests were employed as evaluation tools to measure changes in participants' knowledge before and after the socialization sessions. The results indicated an improvement in the participants' understanding, as reflected by an increase in the average pretest score from 85.71 to a posttest average score of 87.14. However, among the variables assessed in the pretest and posttest, two variables exhibited a decline in average scores, suggesting that participants’ understanding of these specific aspects requires further attention and improvement.